The Effect Of Audio Spiritual Relaxation Towards Reducing Anxiety In Pre Op Sectio Cesaria Patients At Dian Husada Mojokerto Hospital - Nanik Nur Rosyidah; Kiftiyah Kiftiyah; Anik Supriani (Jurnal MIDPRO, 2021)
Ignorance about surgery and the impact after surgery is one of the causes of a lot of anxiety in preoperative patients. This anxiety is shown through physiological, emotional, and cognitive symptoms. One of the psychotherapy that can be done to overcome anxiety in preoperative patients is with a religious spiritual approach, namely through audio spiritual relaxation. The purpose of this study was to determine the effect of audio spiritual relaxation on reducing anxiety in preoperative cesarean section patients at Dian Husada Hospital, Mojokerto.The type of research used is pre-experimental research with one group pretest-posttest design. The population in this study were all patients with preoperative cesarean section at Dian Husada Hospital Mojokerto as many as 13 respondents. The independent variable in this study was audio spiritual relaxation. The dependent variable in this study is anxiety. The instrument used in this study was a questionnaire. The data analysis technique used is the Wilcoxon Signed Rank Test using the SPSS program.The results of this study indicate that before being given audio spiritual relaxation there were 4 respondents (30.8%) who experienced moderate anxiety and 9 respondents (69.2%) who experienced severe anxiety. Meanwhile, after being given audio spiritual relaxation there were 8 respondents (61.5%) who experienced mild anxiety and 5 respondents (38.5%) who experienced moderate anxiety with statistical test results showing sig. 0.001. From these results it can be concluded that there is an effect of audio spiritual relaxation on reducing anxiety in preoperative SC patients at Dian Husada Hospital, Mojokerto.Seeing the results of this study, it is necessary to have audio spiritual relaxation as psychotherapy in overcoming anxiety in preoperative SC patients. Keywords: anxiety, preoperative SC, audio spiritual relaxation.